2019
DOI: 10.1111/cgf.13716
|View full text |Cite
|
Sign up to set email alerts
|

Augmenting Tactile 3D Data Navigation With Pressure Sensing

Abstract: We present a pressure‐augmented tactile 3D data navigation technique, specifically designed for small devices, motivated by the need to support the interactive visualization beyond traditional workstations. While touch input has been studied extensively on large screens, current techniques do not scale to small and portable devices. We use phone‐based pressure sensing with a binary mapping to separate interaction degrees of freedom (DOF) and thus allow users to easily select different manipulation schemes (e. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 96 publications
(98 reference statements)
0
12
0
Order By: Relevance
“…Several of these techniques rely upon more‐than‐2‐finger gestures or screen‐space widgets that are appropriate for large displays but may not translate well to smaller, mobile displays. For smaller displays, pressure has been used to augment tactile interaction, in particular to separate DOFs when manipulating 3D objects [WBAI17, WBAI19]. In this work, a combination of light and hard touches with one or two fingers were used to independently manipulate translation and rotation along the x‐ and y‐axes or the z‐axis.…”
Section: Survey Of the State Of The Artmentioning
confidence: 99%
See 1 more Smart Citation
“…Several of these techniques rely upon more‐than‐2‐finger gestures or screen‐space widgets that are appropriate for large displays but may not translate well to smaller, mobile displays. For smaller displays, pressure has been used to augment tactile interaction, in particular to separate DOFs when manipulating 3D objects [WBAI17, WBAI19]. In this work, a combination of light and hard touches with one or two fingers were used to independently manipulate translation and rotation along the x‐ and y‐axes or the z‐axis.…”
Section: Survey Of the State Of The Artmentioning
confidence: 99%
“…Researchers have adapted tactile interactions for visualization to different computing platforms (e.g. small displays), in part, by augmenting touch with additional inputs, such as pressure [WBAI19]. Researchers have also shown the utility of dataset‐specific tactile interfaces (e.g.…”
Section: Survey Of the State Of The Artmentioning
confidence: 99%
“…Similarly, DOF separation was also investigated for single-user techniques. Here, related work [22,32,34] showed that a separation of translation and rotation actions can increase performance, outperforming a simultaneous manipulation of all DOFs.…”
Section: Dof Separationmentioning
confidence: 98%
“…According to previous studies, users sometimes express high preferences for decomposing manipulations to accomplish complicated tasks (e. g., separating the motions of translation and rotation). Such DOF separation, which can easily be achieved with low-DOF input devices, favors tasks that require a high amount of accuracy (Bérard et al, 2009;Veit et al, 2009;Wang et al, 2019a). Even for immersive environments, it has been argued that the mouse and keyboard are still essential for data exploration as we cannot totally separate the visualization from other analysis processes that require the use of traditional PC-based tools (Wang et al, 2020).…”
Section: Related Workmentioning
confidence: 99%